Handover enhancement in IP mobility for 6LoWPAN scenario - Abdulrahman, Ahmed Faris (2016)
There are an enormous number of applications that could benefit from Wireless Sensor Networks (WSN). One of the main issues is that these applications apply a broad range of exclusive technologies that are difficult to combine with the Internet such as the ability to provide internet services for mobility devices. Therefore, 6LoWPAN was formed to tackle these limitation. The 6LoWPAN nodes were made more flexible and, as such, researchers have enhanced its efficiency by enabling it to move and be mobility node. However, in enabling its mobility feature researchers encountered multiple challenges such as its effect on network lifetime, delays, signaling costs, packet loss, power consumption, and security. Hence, related works sought to reduce the handover delay in order to increase the network lifetime while other works attempted to reduce handover costs and packet loss to achieve optimum handover results. Some of the related works tend to minimize the high percentage of delays in Layer 3 (L3) while others attempt that in Layer 2 (L2). There are also other works reporting on the use of location prediction to obtain the best handover performance. This research focuses on handover delay, packet loss, and handover costs in intra-mobility (micro-mobility) and inter-mobility (macro-mobility) elements of mobile sensor networks. It offers a new framework for 6LoWPAN handover enhancement to reduce the issues noted above. In order to improve handover performance, the research will focus on both L2 and L3. The originality of this research is in the number of thresholds targeted by the coverage area. Two threshold values have been adopted to detect the mobility of the node from Received Signal Strength Indication (RSSI) and Link Quality Indicator (LQI) in handover decision; this concept has not been considered in previous works which depend on only one threshold. The first threshold acts as a mobility detecting factor while the second as a disconnect-reconnect. This research also introduce a timer based method as a signal distribution technique in the handover process. The effects of traffic load for inter-PAN mobility scenario were also investigated. With these approaches, the method can efficiently improve handover performance by minimizing handover delay, packet loss, and handover costs, which is the aim of this project. The analysis of the simulation results with the proposed threshold based approach noted that handover delay is less than the benchmark work by 43.84%. In addition, handover cost is also reduced by 24.93% while the packet loss is minimized by 43.76%.